2013
DOI: 10.1039/c3sm27829h
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent field predictions for quenched spherical biocompatible triblock copolymer micelles

Abstract: We have used the Scheutjens-Fleer self-consistent field (SF-SCF) method to predict the self-assembly of triblock copolymers with a solvophilic middle block and sufficiently long solvophobic outer blocks. We model copolymers consisting of polyethylene oxide (PEO) as solvophilic block and poly(lactic-co-glycolic) acid (PLGA) or poly(ǫ-caprolactone) (PCL) as solvophobic block. These copolymers form structurally quenched spherical micelles provided the solvophilic block is long enough. Predictions are calibrated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…It was found that by implementing a model wherein segments are represented as amorphous beads, i.e. A 60 B 60 A 60 (PLGA 60 PEO 60 PLGA 60 ; 7.5-6.0-7.5 kDa), there exists a set of interaction parameters that leads to structural properties of micelles that compare favourably with the ones found experimentally using the solvent precipitation method [21]. Once such micelles have formed, we envision that the core becomes unresponsive, i.e.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…It was found that by implementing a model wherein segments are represented as amorphous beads, i.e. A 60 B 60 A 60 (PLGA 60 PEO 60 PLGA 60 ; 7.5-6.0-7.5 kDa), there exists a set of interaction parameters that leads to structural properties of micelles that compare favourably with the ones found experimentally using the solvent precipitation method [21]. Once such micelles have formed, we envision that the core becomes unresponsive, i.e.…”
Section: Introductionmentioning
confidence: 78%
“…The method employed, the Scheutjens-Fleer self-consistent field (SF-SCF) theory [16][17][18], successfully used earlier to theoretically study the triblock copolymer micelle structure and stability [19,20]. It was found that by implementing a model wherein segments are represented as amorphous beads, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…8 of our recent paper [36], we investigated whether a hydrophobic polymeric excipient with a chemical composition similar to the hydrophobic blocks of the copolymers used can be encapsulated. In this way we determined the loading capacity/capability and the relation between excipient weight percentage and (hydrodynamic diameter) size.…”
Section: Dls Results Of Single Excipient Homopolymer Loaded Micellesmentioning
confidence: 99%
“…Indeed, during the precipitation procedure we expect the driving force to be an increasing function of the time after the addition of the selective solvent. In the SF-SCF modeling [36] we have simplified this process by taking a simple selective solvent, which presents a moderate driving force for micellisation. This leads to predictions in trends in micelle size and molecular weight which can directly be tested experimentally.…”
Section: Stability; Dynamic Static or Dead/frozen Micellesmentioning
confidence: 99%
See 1 more Smart Citation